Protecting heritage by quantifying the thermal comfort benefits of traditional adobe buildings in Ilorin, Nigeria - Oyebanji, Olutola (2025)
Traditional adobe buildings are often recognized for their lower environmental impact and responsiveness to climate. However, they can be susceptible to erosion and damage caused by exposure to weather conditions, and their maintenance can be laborious and reliant on craft skills passed on through generations. Therefore, they can fall into disrepair and/or replace parts with less laborious materials that may impact their performance. In this work, interventions focused on improving performance and optimizing building fabric to ensure occupant comfort were explored to help safeguard these culturally significant buildings from extinction.